(untitled) (Journal of Organizational Psychology, 2023)
The global rise of electronic payment services necessitates understanding the factors shaping adoption and usage patterns in Egypt, experiencing rapid growth in e-payment and economy. The implications of the interval’s perception of the COVID-19 pandemic and vaccination are noteworthy. To explore these dynamics, a survey was conducted among students and faculty at a public University in Cairo, Egypt. We examined e-payment adoption using frequency of usage, money spent, percentage of expenditures, and an aggregated measure. Among demographics, working status and income had more influence than age, gender, and education. Regression models showed that gender, income, perceived ease of use, perceived risk, and social influence significantly predicted various dependent variables. However, perceived usefulness, incentives, perceived trust, and vaccine importance had limited relevance in e-payment adoption post-COVID-19. Given the limited sample size, further research is recommended.